Dealer behaviour in the Euro money market during times of crisis - Falko Fecht; Stefan Reitz (Applied Economics, 2018)
This article shows how the recent money market disruptions with elevated counterparty risks and uncertainty about the fundamental value of liquidity influenced the trading behaviour of a key dealer in the Euro money market. The complete trading record in the unsecured segment of the money market for 2007 and 2008 is used to estimate a stylized pricing model, which explicitly accounts for the over-the-counter structure. The empirical results suggest that the market maker learns from order flow, but this information aggregation was increasingly hampered as the crisis unfolded.
Keywords: E43; G15; C32; 330; Euro money market; financial crisis; market microstructure; pricing behaviour